Relationships between obstructive sleep apnea and anxiety. Issue 6 (November 2016) - Diaz, Shanna V.; Brown, Lee K.
Abstract : Purpose of review: To summarize recent research investigating the interaction between obstructive sleep apnea (OSA) and anxiety, and contextualize their bidirectional relationship. Recent findings: Recent investigations corroborate the bidirectional relationship between sleep-disordered breathing (SDB) and anxiety, evaluate the etiological and clinical manifestations through different mechanisms, and provide insight into clinical implications of this interaction. Much of the literature about anxiety as it relates to SDB is from small samples, using different tools of symptom measurement that are often subjectively quantified. The objective severity of OSA does not appear to be associated with subjectively reported sleepiness and fatigue, whereas physiological manifestations of anxiety are associated with the severity of subjective symptoms reported. Recent findings support that women are more likely to have comorbid SDB and anxiety than men. SDB may precipitate and perpetuate anxiety, whereas anxiety in OSA negatively impacts quality-of-life. Treating SDB may improve anxiety symptoms, whereas anxiety symptoms can be an obstacle and deterrent to appropriate treatment. Summary: The interaction between anxiety and SDB is still poorly elucidated. Being aware of the clinical associations, risk factors, and treatment implications for SDB as related to anxiety disorders in different populations can help clinicians with the diagnosis and management of both SDB and anxiety.